2015
DOI: 10.3819/ccbr.2015.100002
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Spatial Memory and the Hippocampus in Food-Caching Chickadees

Abstract: Cognitive abilities have been widely considered as a buffer against environmental harshness and instability, with better cognitive abilities being especially crucial for fitness in harsh and unpredictable environments. Although the brain is considered to be highly plastic and responsive to changes in the environment, the extent of such environment-induced plasticity and the relative contributions of natural selection to the frequently large variation in cognitive abilities and brain morphology both within and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Our results imply differences in cognitive abilities that may be inherited, as individuals from both populations were raised in and had experienced identical environmental conditions from 10 days of age. [66] (p. 3187) Cognitive differences between northern and southern chickadees are nonetheless greater in the wild than in captivity [67,68]. It seems that northern birds push the envelope of their phenotype to achieve higher cognitive performance.…”
Section: Brain Size and Latitude In Other Speciesmentioning
confidence: 99%
“…Our results imply differences in cognitive abilities that may be inherited, as individuals from both populations were raised in and had experienced identical environmental conditions from 10 days of age. [66] (p. 3187) Cognitive differences between northern and southern chickadees are nonetheless greater in the wild than in captivity [67,68]. It seems that northern birds push the envelope of their phenotype to achieve higher cognitive performance.…”
Section: Brain Size and Latitude In Other Speciesmentioning
confidence: 99%
“…There is some preliminary evidence that sleep affects spatial learning in birds. For wild birds, remembering different locations such as home range and (in the case of food-storing birds) the location of food caches is extremely important for survival, especially in harsh environments [ 115 , 116 , 117 ]. In a study of chickens, Nelini et al [ 118 ] found that chicks spent more time asleep after learning a spatial discrimination task.…”
Section: Sleep Affects Avian Performancementioning
confidence: 99%
“…Upon secondary contact and hybridization, the new allele(s) from one parent could be incompatible with new or ancestral alleles from the other parent within the hybrid genome [23,24], causing hybrid breakdown in cognition (figure 1b). No matter the mechanism by which hybridization affects learning and memory, fitness optima [8,32], and therefore fitness effects, are likely to be environment-dependent. If hybrid learning and memory abilities are not well adapted to their environment, then selection may act against hybrids [33,34].…”
Section: Introductionmentioning
confidence: 99%